"Eles passarão, eu passarinho" : o processo migratório das famílias vinculadas ao Programa Integrado Entrada da Cidade de Porto Alegre/RS - Munhoz, Manoela Rodrigues (2015)
This study proposes to evaluate transitory housing strategies in Porto Alegre City Entrance Integrated Program (PIEC). In the PIEC, transitory housing alternatives are used to enable the migration process of awaiting resettlement families in the program housing axis. This is an evaluative formative ex-post survey with mixed (qualitative and quantitative) approach. The study is supported on the critical social theory and has the critical dialectical method as its methodological reference framework, with the categories: historicity, totality and contradiction. The data source is field research carried out through semi-structured interviews with the City Housing Department (DEMHAB) employees, the community leaders and families linked to PIEC, besides statistical sources analysis and the review of official documents from the Ministry of cities, Municipality of Porto Alegre and DEMHAB. As a result, it was identified indissociable relationship between capitalist cities urbanization process and the housing issue conformation, marked by the housing mercantilization. It was verified that the current privatist expansion on urban land aggravattes the historic processes of socio-territorial segregation. About PIEC, the speeches in the interviews point to the need for intersectoral approach, planning and management. Concerning transitory housing alternatives, it was identified: a disconnection between families forwarding process and the resettlement work; the divergent judgement between workers and users regarding the halfway house; the social rent alternative selectivity; the fear of leaving their original region; the Emergency House inadequacy as transitory housing due to long waiting periods without deadline for ending; the study points to the need of planning and implementation reviews in the PIEC, by incorporating new elements that nowadays compose the territory, with proper participation of all those involved, especially users of the housing policy, in order to ensure that the commitment signed more than a decade ago by the Porto Alegre Municipality will be met and expanded.